2014
DOI: 10.1353/lm.2014.0004
|View full text |Cite
|
Sign up to set email alerts
|

“Let Me Die in Your House”: Cardiac Distress and Sympathy in Nineteenth-Century British Medicine

Abstract: This essay examines the prevalence of a romantic discourse (e.g., associated with the genre of romance) in nineteenth-century British treatises on diseases of the heart. The nineteenth century brought remarkable changes to cardiac medicine, from the stethoscope to the sphygmograph, rendering medical practice increasingly clinical. However, case histories of cardiac disorders from this period maintain a surprising frequency of three affective elements: sensationalism (exaggerated, dramatic, and shocking events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This induces society at large to focus on the likelihood that healthcare crises will be resolved by medical interventions, and "dying becomes a medical event rather than a natural event in which medicine plays a part" (Walter, 2017, p. 18). Previous research on genre has shown that the medical genre is shaped by current views of medicine and society (Kennedy, 2014;Aaslestad, 2016). We argue that this medicalisation (Walter, 2017) also influences the documentation of dying, a consequence of which is the alienation of human suffering.…”
Section: A Genre That Makes Death Manageable Uneventful and Sanitisedmentioning
confidence: 99%
See 1 more Smart Citation
“…This induces society at large to focus on the likelihood that healthcare crises will be resolved by medical interventions, and "dying becomes a medical event rather than a natural event in which medicine plays a part" (Walter, 2017, p. 18). Previous research on genre has shown that the medical genre is shaped by current views of medicine and society (Kennedy, 2014;Aaslestad, 2016). We argue that this medicalisation (Walter, 2017) also influences the documentation of dying, a consequence of which is the alienation of human suffering.…”
Section: A Genre That Makes Death Manageable Uneventful and Sanitisedmentioning
confidence: 99%
“…Unlike literary texts, Pomata (2014) argues, medical texts are part of an epistemic genre that has evolved in relation to science because their main purpose is to transmit knowledge about a patient and treatment rather than producing meaning as such. Another relevant aspect of medical texts as a genre is found in Kennedy's analysis of medical cases from patients with heart failure in the nineteenth century (Kennedy, 2014). She discovered that although medical realism and clinical discourses are ubiquitous in medical texts, the genre sometimes "displays a range of discursive approaches beyond the clinical by expressing empathy towards the patient's condition" (p. 106).…”
mentioning
confidence: 99%
“…One of the tracings reproduced by Greenlees (1887 : 483) is striking in its inscription of the event of death itself, captioned ‘Dying from a series of Epileptic fits’. Here, the instrument takes on an almost supernatural quality, illustrating ‘the drama of the heart for Victorian physicians’ ( Kennedy, 2014 : 116). Patients with relatively rare diagnoses also provoked interest: in the 1880s a male West Riding patient diagnosed with locomotor ataxia had three tracings taken before being discharged.…”
Section: The Use Of Technology In the Asylummentioning
confidence: 99%